Challenges in the diagnosis and management of simultaneous bilateral toxic anterior segment syndrome after phacorefactive surgery - Ruiz-Lozano, Raul E.; Ramos-Davila, Eugenia M.; Garza-Garza, Lucas A.; Gonzalez-Godinez, Sara; Rodriguez-Garcia, Alejandro (Digital Journal of Ophthalmology, 2023)
A 59-year-old woman presented with a 24-hour history of severe, bilateral, painless vision loss starting 1 day after immediately sequential, bilateral, phacorefractive surgery with multifocal intraocular lens (IOL) implantation at another institution. Best-corrected visual acuity was counting fingers at 1 foot in the right eye and 20/100 in the left eye. Slit-lamp evaluation showed a dense fibrin membrane on the anterior surface of the IOL and significant anterior chamber inflammation in both eyes. B-scan ultrasound revealed bilateral vitreous haze, without membrane formation. The rapid onset, absence of sharp pain, ciliary injection, conjunctival chemosis, eyelid edema, and erythema raised suspicion for bilateral toxic anterior segment syndrome. Significant clinical improvement after high-dose prednisone and hourly prednisolone acetate eye drops supported the diagnosis. After 6 months of tapering anti-inflammatory therapy, optical coherence tomography of the macula showed no pathologic changes, and the patient’s best-corrected visual acuity improved to 20/25 in both eyes.